SUPPLY CHAIN ANALYSIS OF STRAWBERRY PLANTS: A CASE STUDY OF SWEETBERRY AGROTOURISM, CIPANAS, CIANJUR REGENCY - Aulia, Via Nisa; Hanifah, Hana; Fiqri, Arrifa Aulia (Jurnal Hexagro, 2026)
The development of horticultural agribusiness integrated with agrotourism has become an alternative strategy to increase product value added and strengthen rural economies. This study examines the supply chain management of strawberry agribusiness at Sweetberry Agrotourism, Cianjur Regency, which integrates horticultural production with tourism activities. Strawberries are high-value, highly perishable commodities; therefore, efficient, integrated supply chain management is essential to maintain product quality and business sustainability. This study aims to analyze the structure of the strawberry supply chain, identify constraints in product and information flows, and formulate appropriate supply chain management strategies. A qualitative case study approach was employed using primary data collected through in-depth interviews and direct observation involving key informants, namely the General Manager and Farm Manager. The results show that Sweetberry Agrotourism operates a relatively short, integrated supply chain through direct sales to consumers via a pick-your-own tourism concept, which helps maintain freshness, reduce distribution costs, and strengthen producer–consumer interaction. However, supply chain management still faces constraints in post-harvest handling, limited storage facilities, short product shelf life, and fluctuating visitor demand. The study concludes that strengthening post-harvest management, diversifying products, and promoting digital marketing are key strategies to improve the efficiency and sustainability of the strawberry supply chain in agrotourism-based agribusiness.